2007
DOI: 10.1097/jto.0b013e31814617c7
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrence and Unfavorable Prognosis in Patients with Stage I Non-small Cell Lung Cancer and a Tumor Diameter of 20 mm or Less

Abstract: Poor differentiation of tumor was the only risk factor for recurrence and an unfavorable prognosis for stage I non-small cell lung cancer patients with tumor diameters of < or =20 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 15 publications
0
40
1
2
Order By: Relevance
“…In this series, no local recurrence of primary lung cancer was seen and 5-year overall survival rate of stage IA primary lung cancer patients was 90.0%. We previously reported that 5-year overall survival of non-small cell lung cancer with stage I (<20 mm) was 91.4% [22]. While the study cohort was not the same, a long-term outcome of thoracoscopic surgery under localization with our device could be considered as reasonable.…”
Section: Discussionmentioning
confidence: 84%
“…In this series, no local recurrence of primary lung cancer was seen and 5-year overall survival rate of stage IA primary lung cancer patients was 90.0%. We previously reported that 5-year overall survival of non-small cell lung cancer with stage I (<20 mm) was 91.4% [22]. While the study cohort was not the same, a long-term outcome of thoracoscopic surgery under localization with our device could be considered as reasonable.…”
Section: Discussionmentioning
confidence: 84%
“…CEA has not been a useful tumor marker in SCLC patients. However in NSCLC 18 studies [8,11,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] reported a statistical significant evidence for the use of CEA as a prognostic marker in NSCLC patients while 7 [31][32][33][34][35][36][37] were negative.…”
Section: Discussionmentioning
confidence: 99%
“…In the lung, it is often difficult to determine the relative amount of invasive tumor in the setting of a grossly noted mass that may have a significant in situ component. Such difficulty is most often discussed in the context of invasive adenocarcinomas with prominent lepidic growth where adjusted tumor size correlates with improved prognosis in both pathologic and radiologic studies [3,7,22,23,25]. Although the same issue exists in the context of endobronchial exophytic bronchogenic squamous carcinomas, an analogous problem to adenocarcinoma arises in peripheral squamous carcinoma [14,16,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…One aspect of the histologic evaluation of squamous carcinoma that has been noted to resemble lepidic growth of adenocarcinoma is the ability of squamous cell carcinomas to grow on alveolar basement membranes and within alveolar spaces in a nondestructive fashion by solid cohesive aggregates of neoplastic squamous epithelium [13][14][15][16][17][18][19][20][21]. This pattern of growth could confound the adequacy of size-based T staging for squamous carcinomas as it has for small adenocarcinomas of the lung [22,23]. To determine if there is a foundation for such an adjustment of tumor diameter, we reviewed the histologic growth patterns of peripheral squamous cell carcinomas treated by lobectomy at the University of Pittsburgh (Pittsburgh, PA) with a secondary focus on whether the staging for squamous carcinomas could be affected by an alveolar filling component.…”
Section: Introductionmentioning
confidence: 99%